Konstruksi Makna melalui Metafora Konseptual dalam Ama Samawa - Wawan Hermansyah (Ruang Kata, 2026)
Ama Samawa is a traditional proverb of the Samawa community that embodies cultural values, life experiences, and worldviews passed down through generations. Most Ama Samawa expressions are constructed through metaphorical language that draws upon natural elements, social activities, and everyday experiences as vehicles for meaning-making. This study aims to describe how meaning is constructed through conceptual metaphors in Ama Samawa and to reveal the worldview of the Samawa people as represented in these expressions. The study employed a descriptive qualitative approach based on the Conceptual Metaphor Theory proposed by Lakoff and Johnson. The data consisted of 42 Ama Samawa proverbs collected through documentation, literature review, and interviews with cultural informants. Data analysis involved identifying metaphors, determining source and target domains, conducting conceptual mapping, and interpreting culturally. The findings reveal five dominant conceptual metaphors underlying meaning construction in Ama Samawa: (1) life is a journey and ascent, (2) power is height, (3) morality is balance, (4) humans are mirrors for one another, and (5) sustenance is a predetermined share. These findings indicate that the Samawa people understand abstract concepts through concrete experiences derived from their natural environment, economic activities, and social relationships. Therefore, Ama Samawa functions not merely as traditional proverbs but also as representations of the conceptual system and worldview of the Samawa community. This study contributes to the development of cognitive linguistic research grounded in local culture and supports efforts to preserve the cultural heritage of the Samawa people